Sports Marketing Strategies: Membangun Awareness & Public Interest Terhadap Olahraga Baru “Fullball” - Permata, Galih Setyo; Fithroni, Hijrin; Khuddus, Lutfhi Abdil; Wismanadi, Himawan (Universitas Hamzanwadi, 2024)
This research aims to explore marketing strategies to build awareness of the new sport of fullball and identify the interests of fullball community members in Jakarta. This research uses a qualitative method with a phenomenological design approach, data analysis using Milles and Hubermen assisted by Nvivo 12 software. Data collection techniques include observation, interviews with fullball stakeholders as well as fullball community members, and documentation. Data analysis techniques include data reduction, data presentation, conclusion drawing. this research, the research subjects are founders, marketers of Fullball sports regarding sports marketing strategies implemented to build public awareness of Fullball sports. the findings of this research focus on increasing exposure to Fullball sports. The findings of this research focus on increasing exposure through various media channels with content marketing on social media platforms, organising various events, collaboration with influencers, relationships with media and brands, and roadshows. These activities increase fullball's visibility in the eyes of the public and active engagement with the community, as key in building strong awareness and attracting public interest. Members of the fullball community have various motives, including the desire to improve physical fitness, seek fun and entertainment, expand social networks, explore their potential as athletes, and achieve.